1987
DOI: 10.1002/ccd.1810130404
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of visual estimate with digital caliper measurement of coronary artery stenosis

Abstract: We compared visual estimate and digital caliper measurement of coronary stenoses, utilizing both a 50% and 70% diameter reduction as a definition of significance and both experienced angiographers and cardiology fellows as readers. Ten angiograms were interpreted twice, using the different methods, by four readers, two months apart. The angiograms were divided into 12 vessel segments. Stenoses were judged more severe by visual estimate in 11 segments. Seven of twelve segments had significant differences betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Not surprisingly, visual interpretation of coronary arteriograms has been shown to be inaccurate. [10][11][12] Fleming et al 10 demonstrated in 241 coronary studies that 38% were significantly overestimated by visual interpretation. Another study by Schwieger et al 11 compared four interpreters' measurements of coronary stenosis using both a digital caliber computer program and visual estimation.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, visual interpretation of coronary arteriograms has been shown to be inaccurate. [10][11][12] Fleming et al 10 demonstrated in 241 coronary studies that 38% were significantly overestimated by visual interpretation. Another study by Schwieger et al 11 compared four interpreters' measurements of coronary stenosis using both a digital caliber computer program and visual estimation.…”
Section: Discussionmentioning
confidence: 99%